The role of the metabotropic glutamate receptor 5 in nicotine addiction. (27th December 2021) - Akkus, Funda; Terbeck, Sylvia; Haggarty, Connor J.; Treyer, Valerie; Dietrich, Janan J.; Hornschuh, Stefanie; Hasler, Gregor
Abstract: This review summarizes the evidence for the potential involvement of metabotropic glutamate receptor 5 (mGluR5) in the development of nicotine addiction. Nicotine is consumed worldwide and is highly addictive. Previous research has extensively investigated the role of dopamine in association with reward learning and addiction, which has provided strong evidence for the involvement of dopaminergic neuronal circuitry in nicotine addiction. More recently, researchers focused on glutamatergic transmission after nicotine abuse, and its involvement in the reinforcing and rewarding effects of nicotine addiction. A number of robust preclinical and clinical studies have shown mGluR5 signaling as a facilitating mechanism of nicotine addiction and nicotine withdrawal. Specifically, clinical studies have illustrated lower cortical mGluR5 density in smokers compared to nonsmokers in the human brain. In addition, mGluR5 might selectively regulate craving and withdrawal. This suggests that mGluR5 could be a key receptor in the development of nicotine addiction and therefore clinical trials to examine the therapeutic potential of mGluR5 agents could help to contribute to reduce nicotine addiction in society.